Mauritania Country Economic Memorandum : Accelerating Growth Through Diversification and Productive Cities - World Bank (World Bank, Washington, DC, 2020)
The Mauritanian economy is at an important crossroad. Despite significant increases in itsnatural resource wealth, economic development in Mauritania remains weak. The over-reliance on natural resources has left the economy undiversified with growth, exports, and fiscal revenues all dependent on extractives. Responding to the 2015 commodity price shock, the authorities implemented a strong fiscal consolidation program that restored macroeconomic stability andsteered the economy onto a recovery path. The new administration—appointed following the election in mid-2019—now has the challenge and opportunity to map out a more sustainable development model and steer the economy onto a path of accelerated and equitable economic growth for the rapidly growing population. The objective of this report is to support policy makers in Mauritania in their reform efforts to accelerate growth as outlined in the National Development Plan (SCAPP).It attempts to answer the following questions: (i) Why Mauritania could not diversify its economy in the past and what are the opportunities to do so in the future? (ii) What are the reasons behind the weak link between urbanization and growth, and is Nouakchott lifting its weight as anurban agglomeration? (iii) Which policy actions could help build those pathways? By answering these questions, the report aims to contribute to the economic discussion and provide policy recommendations for the choices that Mauritania is facing to accelerate growth and improve theliving standards of its population. The report is organized around five chapters. Chapter 1starts with a brief introduction. Chapter 2 analyzes the key characteristics of Mauritania’s past growth performance. Chapter 3 evaluates the current and future potential for economic and export diversification. Chapter 4 examines the challenges that are preventing urbanization from contributing to growth, with a focus on Nouakchott. Chapter 5 concludes by proposing a menu of policy recommendations that could help Mauritania achieve faster and more sustainable economic growth.